Corporate Volunteering Climate: Mobilizing Employee Passion for Societal Causes and Inspiring Future Charitable Action - Rodell, Jessica B.; Booth, Jonathan E.; Lynch, John W.; Zipay, Kate P. (Academy of Management Journal, 2017)
Today’s corporations are increasingly engaging in efforts to address societal concerns ranging from hunger and poverty to education and financial stability, predominantly through corporate volunteering. Yet, because research has been focused on the individual volunteer we still know relatively little about how corporate volunteering can help address grand challenges. In this study, we introduce the concept of “corporate volunteering climate” in order to examine the broader, more system-level functioning of corporate volunteering in workplaces. Drawing on the sensemaking process, we theorize about how this climate develops—to what extent is it driven by company-level policies versus employee convictions for a cause? We also explore the potential influence of corporate volunteering climate for volunteers and non-volunteers, in terms of the workplace (through employee affective commitment) and the community (through employee intentions to volunteer, whether through corporate opportunities or personally). The results of a study conducted with United Way Worldwide suggest that corporate volunteering climate arises through both employee belief in the cause and corporate policies, and that these forces act as substitutes for each other. Moreover, by fostering a sense of collective pride among employees, this climate is related to affective commitment, and corporate and personal volunteering intentions.